Black Atlantic religion : tradition, transnationalism, and matriarchy in the Afro-Brazilian Candomblé - Matory, James Lorand (Princeton University Press, 2005)
Candomblé is an Afro-Brazilian religion with major counterparts in Nigeria, Benin, Haiti, Cuba, Trinidad and the US, utilising sacrifical rituals and spirit possession to persuade the gods to empower and defend their followers.